Antimalarial and antitumour activities of the steroidal quinone-methide celastrol and its combinations with artemiside, artemisone and methylene blue - Ng, Jerome P. L.; Han, Yu; Yang, Li Jun; Birkholtz, Lyn-Marie; Coertzen, Dina; Wong, Ho Ning; Haynes, Richard K.; Coghi, Paolo; Wong, Vincent Kam Wai (Frontiers in Pharmacology, 2022)
Artemisinin, isolated from the traditional Chinese medicinal plant qīng hāo 青蒿 (Artemisia annua) and its derivatives are used for treatment of malaria. With treatment failures now being recorded for the derivatives and companion drugs used in artemisinin combination therapies (ACTs), new drug combinations are urgently required. The amino-artemisinins artemiside and artemisone display optimal efficacies in vitro against asexual and sexual blood stages of the malaria parasite Plas¬modium falci-parum (Pf), and are active against tumour cell lines. In continuing the evolution of combinations of the amino-artemisinins with new drugs, we examine the triterpenoid quinone methide celastrol isolated from the traditional Chinese medicinal plant léi gōng téng 雷公藤 (Tripterygium wilfordii). This compound is redox active, and has attracted considerable attention because of potent biological activities against manifold targets. We report that celastrol displays good IC50 activities ranging from 0.50 – 0.82 µM against drug-sensitive and resistant asexual blood stage Pf, and 1.16 and 0.28 µM respectively against immature and late stage Pf NF54 gametocytes. The combinations of celastrol with each of artemisone and methylene blue (MB) against asexual blood stage Pf are additive. Given that celastrol displays promising antitumour properties, we examined its activities alone and in combinations with amino-artemisinins against human liver HepG2 and other cell lines. IC50 values of the amino-artemisinins and celastrol against HepG2 cancer cells ranged from 0.55-0.94 µM. Whereas the amino-artemisinins displayed notable selectivities (SI>171) with respect to normal human hepatocytes, in contrast, celastrol displayed no selectivity (SI<1). The combinations of celastrol with artemiside or artemisone against HepG2 cells are synergistic. Given the promise of celastrol, judiciously designed formulations or structural modifications are recommended for mitigating its toxicity.